Influence of neighborhood-level factors on social support in early-stage breast cancer patients and controls. (May 2016) - Thompson, Tess; Rodebaugh, Thomas L.; Pérez, Maria; Struthers, James; Sefko, Julianne A.; Lian, Min; Schootman, Mario; Jeffe, Donna B.
Abstract: Rationale: Low social support has been linked to negative health outcomes in breast cancer patients. Objective: We examined associations between perceived social support, neighborhood socioeconomic deprivation, and neighborhood-level social support in early-stage breast cancer patients and controls. Methods: This two-year longitudinal study in the United States included information collected from telephone interviews and clinical records of 541 early-stage patients and 542 controls recruited from 2003 to 2007. Social support was assessed using the Medical Outcomes Study Social Support Survey (MOS-SS). Residential addresses were geocoded and used to develop measures including neighborhood social support (based on MOS-SS scores from nearby controls) and neighborhood socioeconomic deprivation (a composite index of census tract characteristics). Latent trajectory models were used to determine effects of neighborhood conditions on the stable (intercept) and changing (slope) aspects of social support. Results: In a model with only neighborhood variables, greater socioeconomic deprivation was associated with patients' lower stable social support (standardized estimate = −0.12, p  = 0.027); neighborhood-level social support was associated with social support change (standardized estimate = 0.17, p  = 0.046). After adding individual-level covariates, there were no direct neighborhood effects on social support. In patients, neighborhood socioeconomic deprivation was associated with support indirectly through marriage, insurance status, negative affect, and general health. In controls, neighborhood socioeconomic deprivation was associated with support indirectly through marriage ( p  < 0.05). Conclusion: Indirect effects of neighborhood socioeconomic deprivation on social support differed in patients and controls. Psychosocial and neighborhood interventions may help patients with low social support, particularly patients without partnered relationships in deprived areas. Highlights: In cancer patients, neighborhood deprivation was associated with lower social support. In cancer patients, neighborhood-level support affected change in social support. Individual-level variables reduced neighborhood factors' direct effects on support. Neighborhood deprivation affected support indirectly through several variables. Indirect effects of neighborhood deprivation differed in patients and controls.